Health-Related Quality of Life and Influencing Factors of Pediatric Medical Staff During the COVID-19 Outbreak - Huang, Feng; Yang, Zhe; Wang, Yue; Zhang, Wei; Lin, Yan; Zeng, Ling-chao; Jiang, Xun; Shang, Lei (Frontiers in Public Health, 2020)
Objective To evaluate the health-related quality of life (HRQoL) status and explore its associated factors in pediatric medical staff during the COVID-19 epidemic so as to provide fundamental evidence for clinicians and administrators to formulate targeted intervention measures to improve the HRQoL and mental health status in pediatric medical staff during this, and future, pandemics. Methods A cross-sectional study was conducted to investigate the HRQoL of pediatric medical staff. Univariable and multivariable logistic regression were used to analyze the associated factors. Results A total of 2,997 participants were recruited. Females scored worse than males in terms of emotional functioning (OR=1.6, 95%CI: 1.2-2.1) and cognitive functioning (OR=1.4, 95%CI: 1.1-1.8). The respondents aged 30-39 years and 40-49 years scored worse in nearly all domains of HRQoL compared health care professionals under 30 years old. Respondents with high education had lower scores in physical functioning (OR=1.3, 95%CI: 1.0-1.7) and emotional functioning (OR=1.5, 95%CI: 1.2-1.9). Compared with doctors, nurses had higher scores in all domains except for summary score and worry. The respondents whose working places had not set up pediatric fever clinics and isolated observation areas independently had better scores in all domains except for worry. The respondents who had ever treated patients with COVID-19 had lower scores in all domains. Conclusion During the COVID-19 outbreak, the HRQoL of pediatric medical staff decreased. The factors associated with HRQoL can be used to develop intervention to improve HRQoL in pediatric medical staff.